Pemberdayaan Posyandu Remaja Melalui Kegiatan Senam Sehat untuk Meningkatkan Kesadaran Hidup Sehat - Ananto Utomo; Salman Nuruzzaman; Nurul Istiqomah; Meila Wijayanti; Luthfi Qoriatul Hasanah; Kamila Sofiana Rohmah; Ella Ilham Nur Halimah; Dinda Pranita Putri; Diana Khoirunnisa; Aqilla Fadia Eka Putri; Annisa Nur Hasanah; Anisa Ramadhani; Sandrina Samantha (Journal of Community Service and Engagement, 2025)
The Youth Health Post is a strategic platform for health promotion and prevention efforts. Low physical activity levels, unbalanced diets, and minimal youth participation in community-based health activities are the main issues that need to be addressed. This community service activity was conducted by students from the UIN Raden Mas Said Surakarta Community Service Program (KKN) in Baturan Village, Gantiwarno Sub-district, Klaten District, with the aim of enhancing awareness of healthy living through the empowerment of the Youth Health Post. The method used was descriptive qualitative, involving coordination, simple health checks (LILA, blood pressure measurement, and administration of TTD), group healthy exercises, and health education sessions. The results showed an increase in the enthusiasm and participation of adolescent girls in Posyandu activities. Healthy exercises proved to be an effective means of fostering healthy living habits, while health education and check-ups enhanced adolescents' knowledge about anaemia prevention and the importance of physical activity. Challenges included coordination with schools and villages, limited resources, and difficulties in consistently gathering adolescents. Overall, the activity effectively increased awareness of healthy living and strengthened the role of the Youth Health Post as a community empowerment centre.